Fair insurance guaranty premia in the presence of risk-based capital regulations, stochastic interest rate and catastrophe risk - Duan, Jin-Chuan; Yu, Min-Teh (Journal of Banking & Finance, 2005)
A multiperiod model is developed to measure the costs posed to the guaranty fund in a setting that incorporates risk-based capital regulations, interest rate risk and the possibility of catastrophic losses. The guaranty contract is modeled as a put option on the asset of the insurance company with a stochastic strike price and an uncertain maturity. The impacts of the key factors of this model are examined numerically and shown to make material differences in the costs to the guaranty fund.